Aesthetes component in development kits special clothing - Struminska, T.; Kolosnichenko, M. (Theory and practice of design, 2015)
The article is devoted the analysis of structural-technological decisions and determination of basic descriptions of artistic-aesthetic index of facilities of defence of hands. The basic r equirements for clothing high-visibility. Investigated the influence of artistic and aesthetic performance of special clothes when recruiting.